SOSIALISASI MEMAKAI MASKER, MENJAGA JARAK AMAN, DAN MENCUCI TANGAN (3M) DALAM PENCEGAHAN COVID-19: SOCIALIZATION OF WEARING MASK, KEEPING A SAFE DISTANCE, AND WASHING HANDS (3M) IN COVID-19 PREVENTION - Nandar Wirawan; Reni Reni; Ristiawi Ahmad (STIK KESETIAKAWANAN SOSIAL INDONESIA, 2021)
Prevention of transmission of COVID-19 can start from the family, because the family is the smallest group in the midst of society. With the participation of the family in handling COVID-19, it will have a positive impact in preventing the transmission of COVID-19. The Rawa Buaya community is an area that is in the red zone of the spread of COVID-19, the community will be directly exposed to the virus. Information and handling is needed to the community so that the community does not get infected with covid 19. Therefore, it is necessary to carry out outreach activities with the topic of the importance of 3M socialization in the prevention of COVID-19 at RT 10 RW 04 Exit of Rawa Buaya, Cengkareng, West Jakarta. positive to let the public know about healthy living in the midst of the COVID-19 pandemic